2017
DOI: 10.3390/coatings7100176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selected Properties of Alder Wood as Functions of Sanding and Coating

Abstract: Abstract:The objective of this study was to optimize the sanding and coating processes of black alder wood to promote and support its use in furniture manufacturing. Two criteria have been applied for process optimization, namely, the minimum surface roughness of the samples and power consumption during sanding as a function of various sanding systems. The surface roughness of the sanded specimens and the power consumption during sanding strongly depends on the grit size used. Two eco-varnishes were applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…Particleboard, fiberboard and wood based materials are widely used in furniture industry and cabinet production. Surface quality and type of the coating material are two significant factors influencing overall quality of the product (Ahola 1991, De Moura and Hernandez 2006, Ramananantoandro et al 2018, Salca et al 2017. It is a well-known fact that coating performance namely adhesion is depended on hygroscopic characteristic of wood composite panels.…”
Section: Introductionmentioning
confidence: 99%
“…Particleboard, fiberboard and wood based materials are widely used in furniture industry and cabinet production. Surface quality and type of the coating material are two significant factors influencing overall quality of the product (Ahola 1991, De Moura and Hernandez 2006, Ramananantoandro et al 2018, Salca et al 2017. It is a well-known fact that coating performance namely adhesion is depended on hygroscopic characteristic of wood composite panels.…”
Section: Introductionmentioning
confidence: 99%
“…When the content of black paste was 5.0%-10.0%, the surface roughness of the coating was higher, and the roughness of the coating increased with the increase of the content of black paste. This was due to the uneven distribution of a large number of carbon black particles and the uneven surface of the coating, resulting in an increase in roughness [21]. The mechanical properties, optical properties, and infrared spectroscopy tests showed that the black paste yielded better properties when its content was 0%-3.0%.…”
Section: Resultsmentioning
confidence: 99%
“…Varnishes present different levels of gloss depending on their type and application system. It was shown that polyurethane and polyacrilic resins retained a high gloss even under thermal stress conditions, while for powder coatings a low gloss level was found [25] [26]. The coating is done by using the water base, melamine or nitricellulose materials.…”
Section: Coatingmentioning
confidence: 99%